Ge nanobelts with high compressive strain fabricated by secondary oxidation of self-assembly SiGe rings. (30th December 2014) - Lu, Weifang; Li, Cheng; Lin, Guangyang; Wang, Chen; Huang, Shihao; Wei, Jiangbin; Lan, Xiaoling; Chen, Songyan; Ou, Haiyan
Abstract: Curled Ge nanobelts were fabricated by secondary oxidation of self-assembly SiGe rings, which were exfoliated from the SiGe stripes on the insulator. The Ge-rich SiGe stripes on insulator were formed by hololithography and modified Ge condensation processes of Si0.82 Ge0.18 on SOI substrate. Ge nanobelts under a residual compressive strain of 2% were achieved, and the strain should be higher before partly releasing through bulge islands and breakage of the curled Ge nanobelts during the secondary oxidation process. The primary factor leading to compressive strain is thermal shrinkage of Ge nanobelts, which extrudes to Ge nanobelts in radial and tangent directions during the cooling process. This technique is promising for application in high-mobility Ge nano-scale transistors.